Relationship Between Medication Literacy and Medication Adherence in Inpatients With Coronary Heart Disease in Changsha, China - Zheng, Feng; Ding, Siqing; Lai, Lin; Liu, Xiaoqing; Duan, Yinglong; Shi, Shuangjiao; Zhong, Zhuqing (Frontiers in Pharmacology, 2020)
Background: Medication literacy may be associated with medication safety, and medication adherence is critical in treating coronary heart disease. Few studies have explored the association between medication literacy and medication adherence in patients with coronary heart disease. The aim was to investigate the status of medication literacy and medication adherence among Chinese inpatients with coronary heart disease, and explore the association between medication literacy and medication adherence. Methods: The study was a cross-sectional survey. Of 470 inpatients with coronary heart disease were recruited from hospitals in Changsha, Hunan, China. Participants’ demographic and clinical data were retrieved from hospital charts. Medication adherence was assessed using the four-item Morisky Medication Adherence Scale. Medication literacy was assessed using the Chinese Version of the Medication Literacy Scale. For univariate analysis, potential factors influencing medication adherence were tested by T-tests, analysis of variance, and the Kruskal–Wallis H test. Binary logistic regression model was conducted with medication adherence as the outcome variable in order to analyze the association between medication literacy and medication adherence in inpatients with coronary heart disease. . Results: Among 512 participants, 470 (91.8%) produced valid responses for the survey. Mean (SD) of medication adherence score was 2.26 (13.6), only13.6% had optimal medication adherence. Mean (SD) of medication literacy score was 7.52 (4.09), participants with adequate medication literacy was 30.2% (142). Binary logistic regression analysis indicated that medication literacy was an independent predictor associated with medication adherence. Participants with adequate medication literacy were more likely to have optimal medication adherence (OR 1.461 [95% CI: 0.114, 0.643]; P=0.005), and participants with a high level of education (OR 0.613 [95% CI: 0.284, 0.694]; P< 0.001), a fewer number of medicines(OR 1.514 [95% CI: -0.631, -0.198]; P< 0.001), having medical insurance (OR 0.770 [95% CI: -1.769, 0.059]; P=0.043), single inpatients were more likely to be adherent (OR 1.655 [95% CI:-0.858, -0.149]; P=0.005). Conclusions: The study indicates a significant association between medication literacy and medication adherence in patients with coronary heart disease. These results suggest that medication literacy is an important consideration in the development, implementation and evaluation of medication adherence interventions.